Stroke in the Setting of Giant Cell Arteritis: A Case Report - S. McDermott; N. Casey; D. J. Robinson; K. M. Tan (Case Reports in Medicine)
We describe an unusual complication of a common disease: stroke presenting in a man recently diagnosed with polymyalgia rheumatica. Initial inflammatory markers were misleading. We discuss pitfalls in diagnosis, and approach to management.